Shelf Life and Quality of Guava cv. Kazi as Affected by Stages of Ripening, Storage Temperature and Wrapping Materials (Progressive Agriculture, 2013)
The experiment was conducted to study the shelf life and quality as affected by different stages of ripening, storage temperature as well as wrapping materials fruits of guava cv. Kazi. All the studied parameters except marketability increased for a certain storage period and then declined due to the effect of stages of ripening and wrapping materials (perforated and non perforated white and black polythene bag), while in case of storage temperature, there was gradual increase of physiological weight loss, sugar content (reducing, non-reducing and total sugar) and TSS content. Marketability decreased markedly with the advancement of storage period. All stages of ripening and all wrapping materials were able to keep fruits in marketable condition for 36 days of storage period. But fruits were in better marketable condition when harvested at stage 3 (ripe, yellowish green in colour and crispy pulp) or wrapped with black non-perforated polythene. 5ºC storage temperature, was able to retain more percentage of fruits in marketable condition with longer storage duration. In case of treatment combinations, fruits harvested at stage 3, stored at 5ºC temperature with black non-perforated polythene had the highest physiological weight loss, sugar content (reducing, non-reducing and total sugar) and TSS content while stage1 fruits stored at 20ºC with no wrapping (control) had the lowest.DOI: http://dx.doi.org/10.3329/pa.v19i2.16906 Progress. Agric. 19(2): 1 - 12, 2008